2013
DOI: 10.1007/s00414-013-0884-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of AM-2201 metabolites in urine and comparison with JWH-018 abuse

Abstract: With respect to the continuous emergence of new synthetic cannabinoids on the market since 2008, evaluation of the metabolism of these compounds and the development of analytical methods for the detection of these drugs including their respective metabolites in biological fluids have become essential. Other than JWH-018 or JWH-073, AM-2201 is one of the frequently identified synthetic cannabinoids in Korea. Recently, in our laboratory, several JWH-018 metabolites have been detected in some urine samples obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 28 publications
6
48
0
Order By: Relevance
“…Previous studies have shown that fluorinated synthetic cannabinoids produce the same metabolites as those of their non-fluoro analogues through hydroxylation and carboxylation [24,25]. Furthermore, our research group concluded that the concentration ratio of N-hydroxylated metabolites is a key factor for distinguishing the abuse of these drugs, especially because the availability of reference standards is limited [26,27]. Because N-hydroxylated metabolites share the same ion transitions, careful column separation is required to quantify respective metabolites.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown that fluorinated synthetic cannabinoids produce the same metabolites as those of their non-fluoro analogues through hydroxylation and carboxylation [24,25]. Furthermore, our research group concluded that the concentration ratio of N-hydroxylated metabolites is a key factor for distinguishing the abuse of these drugs, especially because the availability of reference standards is limited [26,27]. Because N-hydroxylated metabolites share the same ion transitions, careful column separation is required to quantify respective metabolites.…”
Section: Introductionmentioning
confidence: 92%
“…Because N-hydroxylated metabolites share the same ion transitions, careful column separation is required to quantify respective metabolites. However, baseline chromatographic separation of N-hydroxylated metabolites has been achieved in only a few studies [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Urine is the most common matrix for drug testing because of the longer window of detection compared to blood and oral fluid, a higher concentration of metabolites for several days after intake, and a generally larger sample volume. However, SC are highly metabolized and detection of parent SC in urine is rare (19)(20)(21)(22)(23). This is the case for AB-CHMINACA, desmethyl analog of ADB-CHMINACA ( Fig.…”
Section: Adb-chminaca (N-[1′-(aminocarbonyl)-2′2′mentioning
confidence: 99%
“…Under the Act UR-144 and XLR-11 were added to temporary scheduled NPS for 3 years in June 2014 in South Korea. Many studies have been reported on the determination and identification of synthetic cannabinoids in urine samples [7][8][9][10], and several researches on the determination of JWH-018, JWH-073, AM-2201, JWH-122 and MAM-2201 in hair samples were reported [11,12]. However, no study on the distribution of XLR-11 and http://dx.doi.org/10.1016/j.jpba.2015.05.022 0731-7085/© 2015 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%